Managing risk in high assurance systems by optimizing topological resources. Issue 3 (25th August 2017) - Hyden, Paul; McGrath, Richard G.; Moskowitz, Ira S.; Russell, Stephen
Abstract: We explore strategies for manipulating the topology of a network to promote increased and pragmatic high assurance systems. Topology matters to network threats and security, and the relative distance between nodes can impact the rate of dispersion of viruses, as well as access times in denial of service, probing, and insider threat attacks. We suggest methods to separate threatening and threatened nodes with enough hops to reduce and degrade risks. This work provides network analysts with an option to include other measures such as risk assessments to the construction and management of high assurance systems. We consider a scaled down model to demonstrate the proof of concept using artificial data. Specifically, we explore the efficacy of ring networks and the structure that occurs on k ‐hop networks when there are a prime number of nodes. We introduce techniques for the randomization of network topologies to manage real‐time risk and provide a dynamic means to improve network security by increasing technical debt to a potential attacker. Abstract : We explore strategies for manipulating the topology of a network to promote increased and pragmatic high assurance systems. Topology matters to network threats and security, and the relative distance between nodes can impact the rate of dispersion of viruses, as well as access times in denial of service, probing, and insider threat attacks. This work provides network analysts with an option to include other measures such as risk assessments to the construction and management of high assurance systems.